Changes and Challenges of the Concept “Educational Environment” - Pesse, Megana (Pedagogika, 2023)
The concept of a learning environment within the realm of IT and technological sciences has not been adequately integrated with the findings of researchers who argue that not every informational setting around a learner can serve as their learning environment (Jucevičienė, 2013). As a result, the theory of educational and learning environments was created (see Jucevičienė, 2007; 2013). The problematic aspect of this study is related to the literature showing a diversity of treatment of the concept of educational environment by interchanging the terms of learning and educational environment. Therefore, the aim of this study is to highlight the peculiarities of the concept of educational environment in higher education. Using a semi-systematic literature analysis, which consists of 63 publications from 1990 to 2023, the concepts of the learning environment and the educational environment were analysed. Results reveal a comprehensive justification of the complexity of educational and learning environments and synthesize the current state of knowledge. A key proposition is that whether learners recognise potential learning environments depends on the dynamic nature of these environments in terms of learners’ needs, which emerge in the process of the activity. Despite the fact that other researchers reveal a close understanding of a learning environment and an educational environment in terms of their content and the analysed problematics, this study justifies that it is not relevant to treat both concepts as one.